A pilot study to establish feasibility and acceptability of a yoga and self-management education intervention to support caregivers and care receivers with persistent pain - Schmid, Arlene A.; Fruhauf, Christine A.; Fox, Aimee L.; Sharp, Julia L.; Portz, Jennifer Dickman; Leach, Heather J.; Van Puymbroeck, Marieke (Frontiers in Rehabilitation Sciences, 2024)
IntroductionApproximately 75% of caregivers providing unpaid care to family members or friends experience persistent pain. Simultaneously, individuals who require caregiving commonly experience pain. The inherent complexity of pain is enhanced by relationship dynamics of two closely tied individuals (i.e., caregiving dyad = caregivers and care recipients). Currently there are no proven pain interventions that target the caregiving dyad. Thus, the purpose of this pilot study was to assess the feasibility of a new behavioral multi-modal intervention, the Merging Yoga and self-management to develop Skills (MY-Skills) intervention.MethodsEach participant was part of a caregiving dyad and all participants had moderate to severe musculoskeletal pain, a score of ≥4 of 6 on the short mini-mental status exam, were ≥18 years old, sedentary, able to speak English, able to stand, and living at home. Participants were randomized to MY-Skills or the control group. MY-Skills was offered twice a week for eight weeks and each two-hour session included yoga and self-management education developed specifically for caregiving dyads experiencing persistent pain. MY-Skills was group based and developed as an in-person intervention. Due to Covid-19, the intervention was moved online and data are presented for in-person and online cohorts. Benchmarks for feasibility were set a priori, addressing: recruitment, attrition, attendance, safety, acceptability/satisfaction, and study completion.ResultsThirteen participants completed the in-person MY-Skills intervention (caregivers n = 7, care-receivers n = 6) and 18 individuals completed the online MY-Skills intervention (9 dyads). Most participants had pain for ≥10 years. Recruitment and attrition benchmarks for the in-person intervention were not met; yet they were met for the online version. In-person and online MY-Skills intervention attendance, safety, acceptability/satisfaction, and completion exceeded benchmark criteria.DiscussionThe MY-Skills intervention appears feasible and acceptable, however changes to recruitment criteria are necessary. Additional testing and larger sample sizes are required to test efficacy. Trial registrationClinicaltrials.gov, #NCT03440320.